Impact of duration of cardiopulmonary bypass on recovery after open heart surgery - Aladwan, Hayel; Alshoubaki, Wael; Alqaisi, Abdullah Ibrahim; Abuamereh, Hamza A.; Alatoum, Lara M.; Mohd, Ashraf Fadel (International Journal of Advances in Medicine, 2024)
Background: Objective of the study was to examine the impact of cardiopulmonary bypass (CPB) duration on recovery from cardiac surgery. Methods: This is an observational retrospective study. Data from adult cardiac surgical patients presented at Queen Alia Heart Institute (QAHI) in the duration between September 2023 and February 2024 was retrospectively analysed. The impact of CPB duration was examined. Patients were divided into groups according to CPB duration (0 to 60 minutes, 60 to 120 minutes, 120 to 180 minutes, 180 to 240 minutes and 240 to 300 minutes). For each group intra-operative and post-operative variable were examined. The intra-operative variables studied were need for blood transfusion, haemofiltration and intra-aortic balloon pump. The post-operative variables studied were duration of post-operative mechanical ventilation, intensive care unit (ICU) stay, hospitalization time and mortality. Results: Consecutive data of 202 adult cardiac surgical patients (34 females and 168 males) was analysed. Average age of patients was 57.149 years. Average duration of CPB was 109.9 minutes (ranged from 29 to 300 minutes). Half of the patients (50.5%) had CPB duration between 1 and 2 hours. Blood transfusion was needed in 88 patients (43.6%). Haemofiltration was used in 32 patients (15.8%) and intra-aortic balloon pump (IABP) was used in 29 patients (14.4%). The average postoperative time of mechanical ventilation was 34 hours and the average ICU stay was 5.5 days. Chest re-exploration was needed in 30 patients (15%). Hospital stay was on average 12 days and in-hospital mortality was witnessed in 20 patients (9.9%). Patients who had CPB for less than one hour (17.3%) had the lowest incidence of blood transfusion (37.1%), lowest incidence of haemofiltration (8.6%), low incidence of IABP use (11%). They also had lowest incidence of chest re-opening (5.7%), shortest time of postoperative mechanical ventilation (13 hours) and shortest ICU and hospital stay (4.1 and 8.5 days, respectively). There was a significant increase in postoperative sternal re-opening and postoperative mortality when the duration of CPB exceeded 3 hours. Conclusions: Duration of CPB is a key predictor of recovery and outcome of cardiac surgery. Shorter CPB time was associated with earlier extubation, less ICU stay and shorter hospitalisation time. Prolonged CPB was associated with higher rates of complications, delayed recovery, longer ICU stay, protracted hospitalisation and higher mortality rates.